Effectiveness of Video Tutorial Media in Improving Skills in Making Catfish Nuggets for Deaf Children - Esy Amelia (Socrates: Journal of Education, Philosophy and Psychology, 2024)
This study discusses the skills of making catfish nuggets for deaf children. The type of research method is experimental. The purpose of this experimental research method is to prove that the use of video tutorial media is effective in developing skills in making catfish nuggets for deaf children. The type of research used is an experimental method in the form of pre-experimental with one group pretest-posttest design. The subjects of this study were 5 deaf children at SLB N 2 Padang. This experiment was formed from various levels, namely the first stage (pretest) to see the condition of the child's initial ability in making catfish nuggets, the second stage was given (treatment) using video tutorial media, the next third stage was a final ability test to see how far the influence of the actions that had been given (post-test). Data processing using the Wilcoxon Rank Tast test. The average pretest result was 44.40, then the post-test result changed to 81.60. The rank taste value was obtained between the initial ability test and the final ability test 2.032 with Asymp. Sig (2-tailed) 0.042. The probability value obtained from the analysis test is compared with the established probability of α = 0.05. The alternative hypothesis is accepted because the probability < of the established probability of 0.042 < 0.05. So it is proven that the use of video tutorial media is effective in improving the skills of making catfish nuggets for deaf children.